2019
DOI: 10.1038/s41559-019-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

Community richness of amphibian skin bacteria correlates with bioclimate at the global scale

Abstract: Animal-associated microbiomes are integral to host health, yet key biotic and abiotic factors that shape host-associated microbial communities at the global scale remain poorly understood. We investigated global patterns in amphibian skin bacterial communities, incorporating samples from 2,349 individuals representing 205 amphibian species across a broad biogeographic range. We analyzed how biotic and abiotic factors correlate with skin microbial communities using multiple statistical approaches. Global amphib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 74 publications
(88 reference statements)
8
98
1
Order By: Relevance
“…Similarly, a recent study of amphibian skin microbiomes found higher diversity on hosts in environments with colder winters and less stable thermal conditions (i.e., temperate regions [5];). Thus, increasing climatic variability appears to promote coexistence and diversity of external microbiomes, perhaps through ecological succession or dormancy mechanisms [5].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Similarly, a recent study of amphibian skin microbiomes found higher diversity on hosts in environments with colder winters and less stable thermal conditions (i.e., temperate regions [5];). Thus, increasing climatic variability appears to promote coexistence and diversity of external microbiomes, perhaps through ecological succession or dormancy mechanisms [5].…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, a recent study of amphibian skin microbiomes found higher diversity on hosts in environments with colder winters and less stable thermal conditions (i.e., temperate regions [5];). Thus, increasing climatic variability appears to promote coexistence and diversity of external microbiomes, perhaps through ecological succession or dormancy mechanisms [5]. Nottingham et al [69] found that both plant diversity and soil microbiome diversity follow temperature (and elevation) gradients at a regional scale with more species under warmer conditions.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The hydrological regime, nutrient content, temperature conditions and biological interactions depend on the climate (Sabater et al, 2008). Bioclimatic conditions have also been shown to influence the abundance of the bacterial microbiome in amphibian microbiome (Kueneman et al, 2019). Thus, our approach seeks to provide an alternative method for surveillance purposes in addition to vector surveillance since non‐vector transmission (human‐mediated) is also a factor in the spread of the pathogen.…”
Section: Introductionmentioning
confidence: 99%